Accelerating prostate stereotactic ablative body radiotherapy: Efficacy and toxicity of a randomized phase II study of 11 versus 29 days overall treatment time (PATRIOT). (August 2020) - Alayed, Yasir; Quon, Harvey; Ong, Aldrich; Cheung, Patrick; Chu, William; Chung, Hans; Vesprini, Danny; Chowdhury, Amit; Panjwani, Dilip; Pang, Geordi; Korol, Renee; Davidson, Melanie; et al.
Highlights: Weekly SABR had better acute quality of life compared to every other day treatment. There was no difference in late toxicity, quality of life, or biochemical failure. Patients should be offered weekly SABR to improve tolerability of treatment. Abstract: Background: Prostate stereotactic ablative radiotherapy (SABR) regimens differ in time, dose, and fractionation. We report an update of a multicentre, Canadian randomized phase II study to investigate the impact of overall treatment time on quality of life (QOL), efficacy, and toxicity. Methods: Men with intermediate risk prostate cancer were randomized to 40 Gy in 5 fractions delivered every other day (EOD) versus once per week (QW). Primary outcome was proportion of patients experiencing a minimally clinically important change (MCIC) in acute bowel QOL using EPIC. Secondary outcomes were toxicity, biochemical failure (BF), other QOL domains, and the rate of salvage therapy. Findings: 152 men from 3 centers were randomized; the median follow-up was 62 months. Results are described for EOD versus QW. Acute bowel and urinary QOL was reported previously. Late changes in QOL were not significantly different between the two arms. There were 1 (1.3%) vs 3 (2.7%) late grade 3 + GI toxicities ( p = 0.36) and 5 (6.7%) vs 2 (2.7%) late grade 3 GU toxicities ( p = 0.44). Two and 5 patients had BF (5-year failure rate 3.0 vs 7.2%, p = 0.22); 0 and 4 patients received salvage therapy ( p = 0.04). 5-Year OS and CSS was 95.8% and 98.6% with no difference between arms ( p = 0.49, p = 0.15). 3 patients in the QW arm developed metastases. Interpretation: Although we previously reported that weekly prostate SABR had better bowel and urinary QOL compared to EOD, the updated results show no difference in late toxicity, QOL, BF, or PSA kinetics. Patients should be counseled that QW SABR reduces short-term toxicity compared to QW SABR.